Wacana Nasionalisme Dalam Novel Penakluk Badai Karya Aguk Irawan Mn - Khadijah Khadijah (Jurnal Studi Agama dan Masyarakat, 2016)
Nationalism is a crucial issue in this republic, where nationalism does not have function as unity tool, because of less carrying to Indonesia itself and there are a few people or groups who underline the nationalism for their own importance, and also because of the pancasila fading spirit which then breinging this nation into separation and all of others issues. A moslem literate Aguk Irawan MN, spent his idea about nationalism phenomenon through novel entitled Penakluk Badai the novel took a setting at rising and base of the nation of Indonesia on pre-independence period and telling about how were the national movement started by the Islamic leader. The method of this study was discourse analisys method based on Halliday model, where this model involved three units of study such as discourse site, discourseinvolvement, and discourse mode. So hten the result of the writer’s study to three analysis unit of Halliday model were the discourse site related to the natives’ education an the fight to colonialism.